IMMUNOREGULATORY IMBALANCE AND FUNCTIONAL STATE OF THE HEART IN THE PATIENTS WITH DIABETES MELLITUS TYPE 2 - I. V. Kologrivova (SPb RAACI, 2018)
Diabetes mellitus type 2 is one of the most important non-infectious diseases in the modern world, being an important risk factor of cardiovascular disorders. Changes in left ventricular myocardial diastolic function are observed in diabetic patients independently from other comorbidities. Etiology of the heart failure during diabetes mellitus type 2 is multifactorial, exhibiting cellular,  molecular and metabolic aspects. However, its pathophysiological mechanisms are not completely understood. The aim of this study was to evaluate numbers of inflammatory T lymphocytes, i.e., T helper type 1 (Th1) and T helper type 17 (Th17) cells, and FoxP3+T regulatory lymphocytes, depending on the functional state of the heart assessed by two-dimensional echocardiography in patients with arterial hypertension and diabetes mellitus type 2. A total of twenty-five patients with a combination of arterial hypertension and diabetes mellitus type 2, and 14 patients with arterial hypertension without carbohydrate disturbances were recruited to a cross-ectional case-control study. All the patients underwent echocardiography with transthoracic access at the M-mode, B-mode and Doppler mode of imaging. We evaluated numbers of Th1 and Th17 lymphocytes by intracellular production of IL-17 and IFNγ by CD4+ lymphocytes, respectively. The numbers of FoxP3+T regulatory lymphocytes were estimated by expression of CD25 and FoxP3 transcription factor. A flow cytometry approach was used in both cases. We revealed some correlations between the numbers of Th17 lymphocytes, FoxP3+T regulatory lymphocytes and functional parameters of myocardium in patients with diabetes mellitus type 2, which were absent in patientswithout carbohydrate impairments. The numbers of FoxP3+T egulatory lymphocytes, Treg/Th17 lymphocyte ratio, and mean fluorescence intensity of IL-17 for Th17 cells was lower in patients with diabetes mellitus and diastolic dysfunction compared to the patients with diabetes free of diastolic dysfunction. Association of diastolic dysfunction with diabetes mellitus type 2 was accompanied by increase of IFNγ+Th1 lymphocyte numbers and concentrations of IL-10, IFNγ and TNFα in serum as compared to the patients with diastolic dysfunction in the absence of carbohydrate metabolism disturbances. The diabetic patients with diastolic dysfunction were characterized by hyperinsulinemia, hyperglycemia, higher index of insulin resistance, increase of waist circumference and visceral adiposity index when compared to the patients with diastolic dysfunction without diabetes. Visceral obesity and decrease of insulin sensitivity may be regarded as pathogenetically significant factors for the development of immune regulatory imbalance and diastolic dysfunction in the patients with diabetes mellitus type 2.